التنوّع الهيكلي للاقتصاد الجزائري وآلية تفعيله لإحداث الإقلاع الاقتصادي –دراسة تحليلية- - ورتي شهرة; موساوي رياض (جامعة الوادي University of Eloued, 2024)
The issue of exit from oil dependency and economic take -off is only a diversity in the production basket, which has become a topic that is of great importance in the Algerian economy, which is the only product in the export process, as development processes are related to the high or low prices of this product (oil) Therefore, the inevitability of diversification of production and the structure of the Algerian economy was not a choice, but rather was imposed to achieve an alternative oil production base that included the stability of the general budget, the flexibility and immunity of the economy, especially after many petroleum shocks (1986 and 2014) As well as the global health crisis Covid19, which caused geographical closure and stops a series of supplies to and from abroad,, where the study aimed to highlight the importance of productive dynamic events at the level of various promising sectors, by highlighting the contributions of the private sector and its role in embodying economic takeoff as a development mechanism in the economy, using the descriptive and analytical approach, where the study concluded that private sector institutions are powerful Acting in the formation of gross domestic product and a mechanism to diversify the production basket and an increase in the added value of the sectors, which allows the raising of exports outside the hydrocarbons.
The structural diversity of the Algerian economy and its activation mechanism to create economic takeoff - analytical study
Keywords: الاقلاع الاقتصادي; القطاع الخاص; المؤشرات الاقتصادية; الجزائر; Economic diversification; Economic take off; private sector; economic indicators; Algeria